Improvement of pulmonary edema and respiratory status after transcatheter PDA closure in the smallest and most premature infants - Chmaisse, Ahmad; Swanson, Kaitlin E.; Ross, Michael M.; Cooper, Matthew L.; Lorant, Diane E.; Alexy, Ryan D. (Frontiers in Pediatrics, 2025)
ObjectiveWe evaluated the effect of transcatheter PDA closure (TCDC) on pulmonary edema by chest x-ray and respiratory status in preterm infants and identified factors contributing to clinical improvement.Study designA retrospective review of TCDC in 68 premature infants from January 2017 to June 2021. Chest x-rays were reviewed to assess pulmonary edema. Multiple clinical characteristics were also evaluated.Results40% of patients weaned respiratory support. x-ray haziness change was not significantly different between groups (p = 0.086), however trended toward significance. 59% had decreased haziness and 16% had a marked decrease. Smaller, younger infants were more likely to wean support and have improved edema.ConclusionChest x-ray haziness improved after TCDC, with smaller infants and earlier closure having more improvement. Infants with lung disease had less noticeable improved edema, indicating the difficulty to assess the hemodynamic significance of their PDA prior to closure. Further studies are needed to identify which neonates benefit most from TCDC.